PENGGUNAAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA PADA MATERI STRUKTUR DAN SIFAT-SIFAT ATOM - Achmad Rante Suparman (Universitas Lambung Mangkurat, 2018)
Abstract. This research aimed to improve activity and students’ academic achievement in Basic Chemistry Course, The material of atoimc structure and their properties. This research used a PTK (Classroom Action Research) where it conducted in cyclical. Each cycle is divided to planning, actualling, observing, and reflecting. The student of The 2016 Mathematics Education taking the basic chemistry about 48 of students are the research sample.Data collecting technique used test and nontest. Data analysis used statistic descriptive. Finding showed that (1) Cooperative Model Group Investigation Type can improve student activity from aspecvisual activities, oral activities, listening activities and mental activities thru two cycles. It can be seen by the first cyclewas 77,08% and 83,33% in the second cycle. (2) Cooperative Model Group Investigation type can be improved the students’ academic achievement from cognitive, effective,and psychomotor aspecs. It can be seen by the first cycle was 72,92% improve in the second cycle 79,17%. Keywords: Group Investigation, activity, study result, Classroom Action Research